Validity of criteria for hospital admission in exacerbations of COPD. Issue 7 (20th February 2014) - Garcia‐Gutierrez, S.; Quintana, J. M.; Bilbao, A.; Unzurrunzaga, A.; Esteban, C.; Baré, M.; Girón Moreno, R. M.; Pulido, E.; Rivas, P.; IRYSS‐COPD Appropriateness Study (IRYSS‐COPD) Group
Summary Aims To validate a previously developed set of explicit criteria for the appropriateness of hospital admission among these patients using the RAND/UCLA Appropriateness Methodology (RAM). Methods We conducted a prospective cohort study of patients experiencing symptoms of COPD exacerbation seen in the emergency departments (ED) of 16 hospitals belonging to the Spanish National Health Service. Sociodemographic and clinical variables needed to assess appropriateness were recorded. Main outcomes were mortality, severe COPD evolution, complications at follow up, and three patient‐reported measures: dyspnoea level, capacity for physical activity and perceived health status. Results Appropriately admitted patients were more likely to die (6.70% vs. 2.68%, p = 0.0102) than inappropriately admitted patients, and were more likely to develop severe evolution (27.09% vs. 6.08%, p < 0.0001) and complications (18.72% vs. 11.92%, p = 0.0244). Among discharged patients, no significant differences were observed in clinical outcomes. All patients exhibited worse dyspnoea and capacity for physical activity after exacerbation, but changes among appropriately admitted patients were less than among appropriately discharged patients. Conclusion Our appropriateness criteria identified patients in worse condition at ED arrival who were more likely to benefit from admission in terms of mortality and COPD evolution.